Association of tirzepatide and the risk of suicide in a real-world cohort - Yu, Wei-Shin; Huang, Jing-Yang; Lo, Shih-Chang; Huang, Chien-Ning; Yang, Yi-Sun; Kornelius, Edy (Frontiers in Psychiatry, 2025)
BackgroundGlucagon-like peptide-1 (GLP-1) receptor agonists, including tirzepatide, are increasingly prescribed for obesity and type 2 diabetes mellitus. Amid safety concerns raised by regulatory agencies regarding potential associations with suicidal ideation or behavior, real-world data on psychiatric risks are critically needed. This study aims to evaluate the association between tirzepatide and suicidal ideation or attempts compared to other anti-obesity medications in a real-world population.MethodsA retrospective cohort study using data from the TriNetX US Collaborative Network, covering 66 healthcare organizations from May 2022 to April 2024. A total of 226,060 patients with overweight or obesity, including 29% with type 2 diabetes, were included. Propensity score matching was applied to compare tirzepatide (N=42,600) with non-GLP-1 anti-obesity medications (N=183,460).ResultsAfter matching, 16,321 pairs were analyzed. The mean age was 48.4 years, and 69.1% were female. Over a median follow-up of 365 days, 17 tirzepatide patients and 33 control patients experienced suicidal ideation or attempts. Tirzepatide was associated with a 48% lower risk of suicide ideation or attempts (aHR: 0.52, 95% CI: 0.28–0.91; P=0.001). Subgroup analyses by BMI, HbA1c, and GFR indicated consistent trends of lower risk. While these findings suggest a potential protective association, the observational nature of this study precludes definitive conclusions regarding causality.ConclusionsTirzepatide use was associated with a lower observed risk of suicidal ideation or suicide attempts compared with other anti-obesity medications. Long-term studies are needed to confirm these findings.